Specialized english for tourism - Cheng, Kiwi (Tổng hợp TP.Hồ Chí Minh, 2016)
This book detailing various travel situations, this guide provides readers with practical dialogues, key expressions, helpful vocabulary, and useful practice exercises. Filled with colorful illustrations, the book also offers a fun, interactive learning experience.